2002
DOI: 10.1161/01.cir.0000032004.56585.2a
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelin-B Receptor System In Vivo Plays a Favorable Inhibitory Role in Vascular Remodeling After Injury Revealed by Endothelin-B Receptor–Knockout Mice

Abstract: Background-Two subtypes of endothelin (ET) receptors, ET

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 40 publications
(43 reference statements)
3
76
1
1
Order By: Relevance
“…This hypothesis was based on previous studies showing that ET-1 stimulates collagen accumulation in aortic and mesenteric vessels in type 1 diabetes and that pharmacological or genetic manipulation of ET B receptors results in augmented intimal remodeling in a carotid injury model (3,4,8,20). This study was designed to examine structural changes in resistance arteries of control and diabetic animals chronically treated with an ET A or ET B receptor antagonist and also to evaluate potential mechanisms of altered matrix dynamics in the microvasculature in diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This hypothesis was based on previous studies showing that ET-1 stimulates collagen accumulation in aortic and mesenteric vessels in type 1 diabetes and that pharmacological or genetic manipulation of ET B receptors results in augmented intimal remodeling in a carotid injury model (3,4,8,20). This study was designed to examine structural changes in resistance arteries of control and diabetic animals chronically treated with an ET A or ET B receptor antagonist and also to evaluate potential mechanisms of altered matrix dynamics in the microvasculature in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the relative role(s) of ET receptor subtypes in mediating vascular remodeling in diabetes was unclear. Murakoshi et al (8) reported that inhibition of the ET B receptor system in a knockout mouse model or pharmacological blockade by an ET B antagonist led to enhanced intimal hyperplasia observed in carotid arteries after injury induced by ligation, suggesting that blockade of the receptor subtype may be detrimental. Thus, this study compared the effects of selective ET A versus ET B antagonism on vascular remodeling in diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of a role of ET B receptors in blood pressure regulation it has been shown that ET B heterozygous (+/−) knockout mice are hypertensive, possibly due to unbalanced activation of ET A receptors by endogenous ET-1 [67]. Also, studies in ET B receptor-knockout mice have suggested that the vascular ET B receptors in vivo may play a favorable inhibitory role in vascular remodeling after injury [68]. ET B receptors are also abundant in tubular epithelium of the renal medulla.…”
Section: Functions Of Et/et Receptorsmentioning
confidence: 98%
“…17,18 The luminal, internal elastic lamina (IEL), and external elastic lamina areas were measured with Scion Image software (Scion Corp). Morphological parameters were calculated as described previously.…”
Section: Morphometric and Histological Examinationsmentioning
confidence: 99%